Analysis of the severity of symptoms of acute diarrhoea caused by rotaviruses in children and the level of parental knowledge about the prevention of this condition - Dorota Kochman; Lisa Szmygel (Innowacje w Pielęgniarstwie i Naukach o Zdrowiu, 2024)
Introduction. Gastrointestinal infections in young children in the form of acute diarrhoea of viral aetiology constitute a serious epidemiological and therapeutic problem.